2013
DOI: 10.4038/sljs.v31i1.5491
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal pancreatectomy: A Sri Lankan experience

Abstract: The surgery was performed under general anaesthesia with the patient in the right lateral position. Five ports were used including the camera port. The positions of ports are shown in figure 2. No abnormality was evident in the peritoneal cavity. The stomach was lifted up using an instrument through the epigastric port. The gastrocolic omentum was divided. A pancreatic mass, involving the tail and compressing the splenic hilum was noted. The pancreas was retracted caudally; the splenic artery was dissected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This report and few other studies have shown that laparoscopic approach is safe and oncologically adequate [ 10 , 11 ]. We have published the first laparoscopic distal pancreatectomy in Sri Lanka in 2013 for a Solid Pseudopapillary Tumour in a young female [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This report and few other studies have shown that laparoscopic approach is safe and oncologically adequate [ 10 , 11 ]. We have published the first laparoscopic distal pancreatectomy in Sri Lanka in 2013 for a Solid Pseudopapillary Tumour in a young female [ 12 ].…”
Section: Discussionmentioning
confidence: 99%